Study of Determination of Turnover Intention Problems in the Digital Era at PT Bandha Graha Reksa Logistik Medan - Fadli, Ahmad; Bhastary, Manda Dwipayani; Martin, Martin; Anita, Anita; Suryani, Ade Erfina (ProBisnis : Jurnal Manajemen, 2023)
The presence of technology in work has an extraordinary positive impact because it can make many jobs easier and at the same time put pressure on a number of employees with very heavy workloads due to demands for automation and fast-paced work. As a result, psychological problems arise, levels of stress and depression, which in turn will result in disruption to employees' mental health, which is something that is found in employees. This condition must be immediately addressed properly by the company considering the impact that will occur on the company where employees with a weak level of resistance will decide to take the decision to resign. Employee mental health problems in this case have an important role which will certainly be a trigger that makes it easier for employees to experience boredom and stress which will lead to the desire to resign from work. The changes that occur also have an impact on the workload currently borne by employees, not only in the form of demands to be able to work by adapting to very rapid changes in technological developments but also the variety of work so that one employee can bear several of the responsibilities of another. Furthermore, employees are also required to quickly complete work on time, which results in employees at work experiencing work pressure due to the changes that are currently occurring. The aim of this research is to describe how much mental health conditions, workload and work pressure encourage employee resignation in the digital era